2014
DOI: 10.1093/bja/aeu228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the laryngoscopy views with the size 1 Miller and Macintosh laryngoscope blades lifting the epiglottis or the base of the tongue in infants and children <2 yr of age

Abstract: NCT01717872 at Clinical Trials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 11 publications
2
49
3
Order By: Relevance
“…In contrast to other studies comparing experienced and inexperienced practitioners [6, 911, 19, 21, 22], this study demonstrated that TTV was similar between the groups. However, in this study, there were no institutional differences in FPA or TTV among the blades or airway scenarios.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies comparing experienced and inexperienced practitioners [6, 911, 19, 21, 22], this study demonstrated that TTV was similar between the groups. However, in this study, there were no institutional differences in FPA or TTV among the blades or airway scenarios.…”
Section: Discussioncontrasting
confidence: 99%
“…Besides, a recently published article in BJA ‘Comparison of the laryngoscopy views with the size 1 Miller and Macintosh laryngoscope blades lifting the epiglottis or the base of the tongue in infants and children <2 year of age provides results similar to our study even though here the Miller blade was introduced from the right commissure of the mouth .…”
supporting
confidence: 85%
“…The differences in infant's airway anatomy compared to an adult further add to it making airway management in lateral position in this age group challenging. Failure to successfully intubate the trachea and secure the child's airway can lead to significant morbidity and mortality in the operative setting . Despite being an important concern, surprisingly so far, there is very limited prospective data on airway management in lateral decubitus position.…”
Section: Introductionmentioning
confidence: 99%